A Faculty Development Framework for Senior High School Teachers Based on Creativity, Skills, and Motivation - Millet T. Mendoza; Frederick A. Inoncillo (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
This study examined the relationship among domain-relevant skills, creative thinking, and task motivation among Senior High School (SHS) teachers using a convergent parallel mixed-methods design. Quantitative data were gathered using the Philippine Professional Standards for Teachers (PPST), Torrance Tests of Creative Thinking (TTCT), and Work Preference Inventory (WPI), while qualitative insights were obtained from focus group discussions and classroom observations. Overall, teachers demonstrated high levels of domain-relevant skills and average levels of creative thinking skills, with relatively stronger performance observed in originality and fluency. In terms of motivation, teachers reported slightly higher levels of intrinsic motivation, particularly enjoyment, compared to challenge, while extrinsic motivation remained average, with compensation rated higher than external recognition. Correlation analysis did not reveal statistically significant relationships among the variables. However, qualitative findings highlighted the influence of both individual and contextual factors. Teachers emphasized intrinsic motivation, instructional practices, and institutional support as contributing to creativity, while also identifying constraints such as limited resources, heavy workloads, and limited professional development opportunities. These findings suggest that teacher creativity appears to be influenced by a combination of personal and environmental conditions rather than strong statistically significant relationships among the measured variables. Based on these findings, a faculty development framework is proposed to support teacher creativity through targeted professional development, improved institutional support, and resource provision, with the goal of fostering more innovative teaching practices.